Sobre el uso del «etcétera» en La Celestina - Patrizia Botta (Celestinesca, 2021)
In Fernando de Rojas’ work there are a lot of quotations of other authors and people's sayings, both learned and popular. In certain cases it is taken for granted that readers do know the proverbs so well that Rojas, with great elegance and reticence, cuts them in halves by adopting the technique of «leaving something unsaid» and utters only the first half of them, using the word «etcétera» to sum up  the  rest. The technique of «leaving  something  unsaid» or «hinted at» by re-placing it with the word «etcétera», though an old tradition, is a true wink at the readers, since it makes them turn to their memory to complete the quotations with their remembrances, so that they can play an active role while reading. On the another hand, this is a very recurring technique in La Celestina (in fact it occupies each of its parts —if we consider the work as «divided» into Act I, Comedia, Tragicomedia, also known as parts A, B, C). Therefore, this is a recurrent stylistic feature throughout the work, the author’s true stilystic feature, which becomes a unifying element of the work so far overlooked in the discussions concerning both the authorship and the stylistic studies about the text.